Effect of antioxidant supplementation on digestive enzymes in radiation induced intestinal damage in rats. (December 2013) - Anwar, Mumtaz; Nanda, Neha; Bhatia, Alka; Akhtar, Reyhan; Mahmood, Safrun
Abstract Purpose: Intestinal mucosa, a rapidly proliferating tissue, is highly sensitive to radiation and undergoes apoptosis as a consequence of over generation of oxidative free radicals and the lack of the antioxidants. Thus the present study was designed to investigate the intestinal damage induced by radiation and to study if supplementation of the diet with antioxidant vitamins could ameliorate the intestinal damage and its digestive activity, as determined by the expression of various border enzymes. Materials and methods: Swiss Albino rats (150–200 g body weight) were divided into six groups. Group I: Control untreated; Group II: Irradiated; Group III: Irradiated + vitamin A; Group IV: Irradiated + vitamin C; Group V: Irradiated + vitamin E; and Group VI: Irradiated + lycopene. Animals were exposed to whole body γ-radiation from 60Co at the rate of 8 Gy for 15 min/rat. Intestinal morphology and changes in various digestive enzymes together with, DNA damage was studied in six groups and each group consisted of 18 animals. Results: The gastrointestinal toxicity resulted in malabsorption, diarrhoea, weight loss, loss of appetite, abdominal haemorrhage and hair loss. The activities of sucrase and alkaline phosphatase were elevated and those of lactase, leucine aminopeptidase (LAP) and gamma-glutamyl transpeptidase or tranferase (γ-GTP) were markedly reduced. Antioxidant vitamin A, C or E supplementations prevented changes in brush border enzyme activities as compared to lycopene administration in rat intestine by radiation exposure. Intestinal histology showed that the vitamin supplementation to irradiated rats minimized the intestinal damage in rats. Conclusion: These findings suggest that the epithelial lining of the intestine is highly sensitive to radiation exposure and supplementation of antioxidant vitamins is helpful in minimizing the intestinal damage and supplementation by vitamin E was most potent in ameliorating the intestinal aberrations.